2007
DOI: 10.1007/s11627-007-9071-4
|View full text |Cite
|
Sign up to set email alerts
|

Disarming and sequencing of Agrobacterium rhizogenes strain K599 (NCPPB2659) plasmid pRi2659

Abstract: Agrobacterium rhizogenes strain K599 (pRi2659), a causative agent of hairy root disease, effectively induces hairy root formation in a variety of plant species, including numerous soybean (Glycine max) cultivars. Because Agrobacterium-mediated transformation of soybean remains challenging and labor intensive, K599 appeared a suitable progenitor for new agrobacteria strains for plant transformation. In this paper, we report the disarming and sequencing of pRi2659 and the usefulness of the resulting disarmed str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 62 publications
0
45
0
Order By: Relevance
“…1) and is preceded by a strong ribosome binding site (RBS [AGGAG]) 8 bp upstream and a favored A at Ϫ3 (20). The RBS, Met codon 808, and the A at Ϫ3 are conserved in three known GALLS genes from pRi1724, pRiA4, and pRi2659 (accession numbers NP_066636, BAB47245, and ABW33585) (23,25). Initiation of translation at Met 808 would yield a protein with a calculated molecular weight of 104,697, which is close to the molecular weight estimated by SDS-PAGE ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1) and is preceded by a strong ribosome binding site (RBS [AGGAG]) 8 bp upstream and a favored A at Ϫ3 (20). The RBS, Met codon 808, and the A at Ϫ3 are conserved in three known GALLS genes from pRi1724, pRiA4, and pRi2659 (accession numbers NP_066636, BAB47245, and ABW33585) (23,25). Initiation of translation at Met 808 would yield a protein with a calculated molecular weight of 104,697, which is close to the molecular weight estimated by SDS-PAGE ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Plasmid pMSA5 carries an incomplete ORF69, which codes for a predicted protein similar (86% identity) to a putative helicase of R. leguminosarum bv. viciae 3841 , and ORF70 which encodes a predicted product with similarity (71% identity) to partitioning protein ParB of A. rhizogenes (Mankin et al, 2007). Plasmid host range studies surprisingly revealed that this minireplicon is able to replicate in both Alphaproteobacteria (Brevundimonas sp.…”
Section: Plasmid Psina Is Responsible For Arsenite Oxidationmentioning
confidence: 99%
“…3, lavender-colored genes). This region, about 94 kb in size, includes ORFs that are annotated as putative unknown opine transport and metabolic genes (90,91). Likewise, the region contains sequences that align with sugar transporters and glycerol metabolism genes (90,91), as well as a large number of hypothetical genes or genes of unknown function.…”
Section: Discussionmentioning
confidence: 99%
“…MAFF 301724, a biovar 1 strain from which pRi1724 was identified, was isolated in Japan from a melon plant with hairy root disease (92,93). The parental strain of pRi2659, also a biovar 1 strain, was isolated in the United Kingdom from a similarly diseased cucumber plant (91). Based on sequence analysis, pRi1724 and pRi2659 are closely related plasmids (90).…”
Section: Discussionmentioning
confidence: 99%